Patient-centered communication in chiropractic education: A cross-sectional survey of chiropractic students in North America - Aubrianna L. Jones; Daphne To; Suzanne Lady; Karin Hammerich; Zakary T. Monier; Kara D. Burnham; Melissa Kolb; Jordan A. Gliedt (The Journal of Chiropractic Education, 2026)
ABSTRACT Objective The primary objective of this study was to explore chiropractic students’ predisposition to patient-centered communication (PCC), focusing on empathy and cultural humility. Methods A survey-based study was conducted across 7 doctor of chiropractic programs in North America. Eligible students were invited to participate in an electronic survey assessing empathy (the revised Kiersma-Chen Empathy Scale) and cultural humility (the Foronda Cultural Humility Scale). Linear regression was used to examine the relationship between (1) doctor of chiropractic program enrollment and empathy and cultural humility and (2) PCC-related coursework completion and empathy and cultural humility. Results A total of 426 responses to the electronic survey were collected (7% response rate). Most participants were enrolled in preclinical coursework (61%) and had completed PCC-related coursework (76%). Empathy was lower among clinical students though not statistically significant (β = −1.20; confidence interval, −2.93 to 0.52; p = .169). No significant associations were found between enrollment status or PCC coursework and either empathy or cultural humility. Conclusion No significant associations were found between PCC-related coursework or enrollment status and empathy or cultural humility. This study highlights an underexplored area within chiropractic education and calls for comprehensive research to characterize the integration of PCC within chiropractic curricula and clinical training.